2018
DOI: 10.3390/ijerph15050928
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Predicting Suicidal Thoughts and Behaviours in a Sample of Rural Australians with Depression

Abstract: Suicide is a leading cause of death, particularly in rural and remote areas. Although depression is strongly related to both suicidal ideation and attempt, it lacks specificity as a predictor, and little is known about characteristics that increase suicide risk among people with depression. A telephone version of the World Mental Health Composite International Diagnostic Interview explored lifetime depression, suicidal ideation, suicide attempt, and related factors among a community-dwelling sample of rural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 25 publications
5
38
0
1
Order By: Relevance
“…This result was consistent with Jeong and Yi’s study [ 44 ], who reported the mediating effect of depression on the relationship of attitude toward psychiatric help and suicidal ideation among 151 adolescents in South Korea. These results also are in line with prior studies that have shown that people with depressive disorders are at least 40 times more likely to die by suicide, and the negative perceptions of psychiatric treatment were negatively related to the treatment of depression [ 45 , 46 ]. Adolescents with suicidal ideation are more likely to be depressed [ 42 ] and depressed adolescents seek professional help less than those without depression [ 47 ]; it is like they get trapped in a vicious circle.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result was consistent with Jeong and Yi’s study [ 44 ], who reported the mediating effect of depression on the relationship of attitude toward psychiatric help and suicidal ideation among 151 adolescents in South Korea. These results also are in line with prior studies that have shown that people with depressive disorders are at least 40 times more likely to die by suicide, and the negative perceptions of psychiatric treatment were negatively related to the treatment of depression [ 45 , 46 ]. Adolescents with suicidal ideation are more likely to be depressed [ 42 ] and depressed adolescents seek professional help less than those without depression [ 47 ]; it is like they get trapped in a vicious circle.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, this study suggests that accurate assessment and intervention of depression be a priority rather than only making adolescents’ attitudes toward psychiatric help more positive, for overall decrease and prevention of adolescent suicide. As previous studies [ 45 , 48 ] suggested, concrete relationships among schools, hospitals, and community systems should be established and parents should be educated about the importance of using professional help for their own and their children’s mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…En este contexto, se ha descrito que la depresión está fuertemente relacionada, tanto con la ideación suicida como con el intento, pero carece de especificidad como predictor, y se sabe poco sobre las características que aumentan el riesgo de suicidio entre las personas con depresión (Handley et al, 2018). Se señala que la gravedad de la depresión posee una relación significativa con las tendencias suicidas tanto en hombres como en mujeres, sin embargo, los intentos de suicidio fueron significativamente más comunes entre las mujeres más jóvenes, sin necesariamente que la depresión estuviera diagnosticada en ellas (Brådvik, 2018).…”
Section: Introductionunclassified
“…Sin Korea . In a sample of rural Australians with depression, 48% reported lifetime suicide ideation, and 16% reported a lifetime suicide attempt [13].…”
Section: Introductionmentioning
confidence: 99%